Comparative outcomes of pars plana vitrectomy with subretinal rt-PA injection in polypoidal choroidal vasculopathy: the role of simultaneous anti-VEGF treatment - Chen, Lulu; Wang, Chuting; Zhang, Wenfei; Meng, Lihui; Sun, Lu; Chen, Youxin (Frontiers in Medicine, 2025)
PurposeThis study aimed to assess the efficacy of simultaneous intravitreal anti-vascular endothelial growth factor (VEGF) with pars plana vitrectomy (PPV), subretinal recombinant tissue plasminogen activator (rt-PA), and pneumatic tamponade in treating submacular hemorrhage (SMH) due to polypoidal choroidal vasculopathy (PCV), compared to the procedure without anti-VEGF.MethodsWe retrospectively analyzed PCV patients with SMH who underwent the procedure at a tertiary hospital from 2021 to 2024. Outcomes comprised alterations in best-corrected visual acuity (BCVA), SMH absorption, and the administration of postoperative anti-VEGF injections.ResultsA total of 31 patients were included in the study. There was no significant difference in best-corrected visual acuity (BCVA) improvement or anti-VEGF usage between the anti-VEGF group and the control group. Both treatment strategies led to improved visual acuity. The mean number of anti-VEGF injections following surgery was 1.0 (8.0) in the anti-VEGF group and 1.0 (6.0) in the control group. Complications such as retinal detachment and recurrent vitreous hemorrhage occurred in both groups, with no significant difference between the groups.ConclusionSimultaneous intravitreal anti-VEGF did not outperform the procedure without it in terms of improved visual acuity or postoperative anti-VEGF usage. Further studies are needed to determine the best treatment approach for PCV patients with SMH.